2002
DOI: 10.1210/en.2002-220193
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Estrogen Receptor Subtypes in Rat Pituitary Gland during Pregnancy and Lactation

Abstract: The aim of this study was to examine whether the expression levels of mRNA of the three estrogen receptor (ER) subtypes, ERalpha, ERbeta, and truncated ER product-1 (TERP-1) found in the rat pituitary gland were modified during gestation, lactation, and postlactation periods. By using relative quantitative RT-PCR, we found that ERalpha mRNA significantly peaked in midpregnancy. However, the ERalpha protein level remained constant. ERbeta gene expression did not change throughout pregnancy, suggesting that it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 59 publications
1
26
1
Order By: Relevance
“…An activation of inhibitory pathways may modulate the steady-state levels of Gαi2 mRNA [27,28]. The relative expression levels of Gα i2 mRNA were semiquantified by RT-PCR with Gi2-S (TCAAACTTAC-TCTGGATGTAGCTG) and Gi2-A (TCAAACTTA-CTCTGGATGTAGCTG), as described elsewhere [29,31]. The reaction condition was as follows: 94 C for 5 min followed by 23 cycles of 94 C for 40 sec, 61 C for 25 sec, and 72 C for 35 sec.…”
Section: Pharmacological Characterization Of Chicken Rfrpr and Npffrmentioning
confidence: 99%
“…An activation of inhibitory pathways may modulate the steady-state levels of Gαi2 mRNA [27,28]. The relative expression levels of Gα i2 mRNA were semiquantified by RT-PCR with Gi2-S (TCAAACTTAC-TCTGGATGTAGCTG) and Gi2-A (TCAAACTTA-CTCTGGATGTAGCTG), as described elsewhere [29,31]. The reaction condition was as follows: 94 C for 5 min followed by 23 cycles of 94 C for 40 sec, 61 C for 25 sec, and 72 C for 35 sec.…”
Section: Pharmacological Characterization Of Chicken Rfrpr and Npffrmentioning
confidence: 99%
“…Rat gonadotropes express both isoforms of ER, the predominant ERa (Lindzey et al 2006) and ERb at nuclear level (Kuiper et al 1997, Mitchner et al 1998, Vaillant et al 2002, Sánchez-Criado et al 2005a. In addition, an ER which appears to be the same protein as nuclear ERa is expressed at the plasma membrane level (Bression et al 1986, Razandi et al 1999, Toran-Allerand et al 1999, Schmidt et al 2000, Kelly & Levin 2001, Simoncini & Genazzani 2003, Toran-Allerand 2004, Levin 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro translated TERP is detected as a pair of doublets at 22-24 kDa, which likely represent translation from two methionines, at amino acids 393 and 408 in exon 5 (28,32). The larger protein is detected preferentially in transfected cells and in normal pituitaries (11,28,29,31,32). The dimerization mutants of ER␣ and TERP, ER␣ L509R and TERP L509R, also interact with GST-REA in a similar fashion (Fig.…”
Section: Terp Binds To Rea and Competes With Er␣ Inmentioning
confidence: 75%
“…However, we found that REA mRNA expression varies less than 2-fold throughout the estrous cycle and is similar to that of ER␣ (data not shown). In contrast, TERP expression changes dramatically in response to E 2 (26,31), during pregnancy (29), and throughout the estrous cycle (Fig. 5B).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation